Electrical and chemical properties of vacancy-ordered lead free layered double perovskite nanoparticles. Issue 9 (16th February 2022) - Sawahreh, Amal; Binyamin, Tal; Jiang, Jie; Millo, Oded; Goldberg, Oren; Azulay, Doron; Pachter, Ruth; Etgar, Lioz
Abstract : In this work we synthesized and investigated the properties of vacancy-ordered lead-free layered double perovskite (LDP) nanoparticles. Abstract : In this work we synthesized vacancy-ordered lead-free layered double perovskite (LDP) nanoparticles. This structure consists of two layers of trivalent metal halide octahedra [B(iii )X6 ] 3− separated by a layer of divalent metal [B(ii )X6 ] 4− (B is a divalent or trivalent metal). The chemical formula of this structure is based on A4 B(ii )B(iii )2 X12 where A is Cs, B(iii ) is Bi, X is Cl and B(ii ) is a different ratio between Mn 2+ and Cd 2+ . Well-defined colloidal nanoplates of Cs4 Cd x Mn1− x Bi2 Cl12 were successfully synthesized. These nanoplates show photoluminescence (PL) in the orange to red region that can be tuned by changing the Cd/Mn ratio. High resolution scanning transmission electron microscopy (HR-STEM) and atomic resolution elemental analysis were performed on these lead free LDP nanoplates revealing two different particle compositions that can be controlled by the Cd/Mn ratio. Ultraviolet Photoelectron Spectroscopy (UPS) and scanning tunneling spectroscopy (STS) reveal the band gap structure of these LDP nanoplates. Density functional theory (DFT) calculations show the existence of [MnCl6 ] 4− in-gap states. While the absorption occurs from the valence band maximum (VBM) to the conduction band minimum (CBM), the emission may occur from the CBM to an in-gap band maximum (IGM), which could explain the PL in the orange to red region of these nanoplates. This work provides a detailed picture of the chemical and electronic properties of LDP nanoparticles.